STRENGTHENING THE ROLE OF CORPORATE CARRIER IN THE DEVELOPMENT OF CORPORATE STUDENTS AT THE CHILDREN'S SPECIAL DEVELOPMENT INSTITUTION - Iqbal Kamalludin; Apriliani Kusumawati; Ratna Kumala Sari; Ayon Diniyanto; Bunga Desyana Pratami (CREPIDO, 2021)
The rehabilitation approach has not become a priority for coaching so that it is difficult to change Andikpas' behavior for the better. This paper aims to describe the idea of strengthening the role of Correctional Caregivers in fostering Correctional Students at the Special Child Guidance Institution. The research method of this paper uses normative juridical with a qualitative approach.  Harmonizing  regulations in the correctional system is needed through legal rules in the form of special guidelines. In addition to increasing knowledge and understanding related to child protection, it is also necessary to strengthen the capacity of counseling techniques. Considering that counseling is one method that can help Andikpas to express various feelings, including the negative thoughts he feels.